(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The main objective of this research is to select the best site for the establishment of a new bridge on the Al Gharraf river within the limits of the Al Muwaffaqiyah region . Al Muwaffaqiyah region is located in Wasit province in Iraq. The study area is divided into multiple zones . Three alternatives are proposed to construct the bridge site. The best one is selected using network analyst tool of ArcGIS software depending on the largest number of routes passing between zones. The route link between both sides of Al Gharraf river in Al Muwaffaqiyah region is one of the important projects in the city. The project will provide a new crossing point on Al Gharraf river . The proposed route will contribute to reduce traffic congestion depending on the foundations of planning and traffic so that gives the desired result of this project in terms of the location and importance of economic feasibility.